Erroneous Portrayal of Black National Question in Ralph Ellison’s Invisible Man - Khatri, Tilak Bahadur (Patan Pragya, 2023)
This article examines the several contradictory aspects of American society that the unnamed black protagonist of Ralph Ellison's novel Invisible Man encounters and that cause him to descend into absurdity. The study has relevance to identify and deal with the different contradictory aspects of American society. The article addresses on the research problems concerning to the protagonist's sufferings and his inability to identify the causes of his sufferings. The study deals with the research problems by applying the research approach (methodology) of historical materialism. In a class-based society, the protagonist, who is of black nationality, is a member of the working class. He is suppressed not only by white people but even by wealthy black people. He receives assistance not only from black people but also from lower-class white people. But he lacks the ability to identify friends from enemies. He wants to free himself and the entire black nationality from all forms of oppression, injustice, and inequality because he is a member of the black race. As a result, he joins the Brotherhood (the communist party), but he quickly leaves because he does not understand its tenets. He declines to join the Black Nationalist party and is unable to identify any alternative organizations that could help end the persecution of black people on a national level. Finally, he loses all hope, starts to perceive disorder around, and makes the decision to leave society. However, while living apart from society, he still sees ways to benefit it, which is an absurdist notion itself. The study reveals that the protagonist's queer theory of absurdism, which he develops at the novel's conclusion, does nothing to further the cause of repressed Afro-Americans; rather, it only serves to fuel their frustration and pessimism.